Pengabdian Masyarakat melalui KKN-T : Edukasi Pengelolaan Limbah Organik menjadi Sabun Cair Ramah Lingkungan - Budi Prabowo; Agnes Lidya Claudya; Annisa Nathania Dewi; Aprilia Rahmasari; Bramantio Sunubrata (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2024)
The management of household waste is an urgent global problem that must be solved to ensure environmental sustainability and human health. However, products available on the market generally contain chemicals that can have a bad impact on health and the environment if used in the long term. The Thematic Community Service Lecture (KKN-T) in Sarirogo Village, Sidoarjo Regency, seeks to improve organic waste management through socialization of the production of organic liquid soap with the socialization method. This method contains the provision of materials, workshops and discussions with village health cadres. This socialization provides useful understanding and skills for the people of Sarirogo Village to utilize organic waste around to realize environmentally conscious village consumption and production in accordance with Sustainable Development Goals (SDGs) 12.